Social-science commentary on the letters of Paul - Malina, Bruce J. (Fortress Press, 2006)
Books of the New Testament / Biblical studies, criticism & exegesis. - Brings to the fore necessary, significant and enlightening ways of understanding the role of Paul and his social dynamics with the churches he founded. Contains new translations and cultural notes as well as maps, diagrams and illustrations.